2022
DOI: 10.30958/aje.9-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Distance Education Experiences of Teacher-Parents during the COVID-19

Abstract: This research aimed to determine the opinions of teacher parents about distance education process during COVID-19. The study was designed as a case study which is one of the methods in qualitative research. The sample of the study composed of 83 teacher parents from different branches in Turkey. Maximum variation and criterion sampling methods were used to select the participants. The data of the study were gathered though open ended questions developed by the researchers and were analyzed through descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Before the pandemic, it has been found that communication between families and schools is beneficial for children’s education and parent satisfaction (Goodall & Montgomery, 2014). Insufficient communication was a reported issue in spring 2020, with parents indicating that they needed communication with the schools that was higher in quality than they were receiving (Güvercin et al, 2022; Jones & Forster, 2021). In our sample, it appears that as parents took on increased roles in education, they also changed in the ways they interacted with teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Before the pandemic, it has been found that communication between families and schools is beneficial for children’s education and parent satisfaction (Goodall & Montgomery, 2014). Insufficient communication was a reported issue in spring 2020, with parents indicating that they needed communication with the schools that was higher in quality than they were receiving (Güvercin et al, 2022; Jones & Forster, 2021). In our sample, it appears that as parents took on increased roles in education, they also changed in the ways they interacted with teachers.…”
Section: Discussionmentioning
confidence: 99%
“…We scanned each article for relevance to our focus on teachers who were also parents during the pandemic lockdowns. Only a single article ( Güvercin, Kesici, & Akbaşlı, 2021 ) was specifically about teacher-parents, so we conducted a close reading of more general articles that might reveal insights into the dual role. From the final 32 articles we synthesised the literature into two themes: teachers as frontline workers and teachers who were also parents.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A further twelve qualitative or mixed method studies provided some relevant insights, where respondents mentioned their dual roles as teachers and parents during this time. One qualitative Turkish study ( Güvercin et al, 2021 ) focused on the “double-sided” role of teacher-parents, highlighting that, for home learning to be successful, teachers needed the support of parents and parents needed the support of teachers. Two other studies found that having younger children at home increased stress and anxiety ( Allen et al, 2020 ; Košir et al, 2020 , pp.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are multiple styles of online infrastructure that have been prepared for the teachers and educatorsto implement. The affordability and accessibility needs to be focused primarily in under developed countries to make on-line system successful (Güvercin et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%